Evaluation of pre-cycle hysteroscopy findings and its pathological results of 458 patients undergoing IVF: A retrospective cohort study - Demirdag, Erhan; Kutlucan, Hazal; Safarova, Sahila; Guler, Ismail; Akdulum, Munire Funda Cevher; Bozkurt, Nuray; Erdem, Mehmet; Erdem, Ahmet (Annals of Medical Research, 2022)
Aim: To evaluate the hysteroscopy results performed before IVF treatment and its pathological findings that may affect pregnancy outcomes in patients undergoing the first IVF cycle. Materials and Methods: This descriptive study was carried out retrospectively at Gazi University Hospital and a private IVF Clinic between January 2016 and December 2021. A total of 458 patients who had hysteroscopy procedures prior to the planned IVF cycle were analyzed. Appropriate surgery was performed simultaneously during hysteroscopy in patients with uterine cavity abnormalities. Outcome measures were the frequency of uterine abnormalities detected during the hysteroscopy and confirmation of these abnormalities with their pathological findings. Results: Unexplained infertility was the most frequent infertility etiology among patients (50.9%). The most finding abnormality was endometrial polyp detected in 45.2% of patients during hysteroscopy. The second frequent abnormal finding was intrauterine adhesion, with a ratio of 15.9% of patients. The uterine cavity was seen as normal in 9.6% of patients during the hysteroscopy procedure. Endometrial sampling was performed in 75.5% of patients. The most common pathological result was endometrial polyp that was consistent with hysteroscopy findings (44.3%). Only 20.8% of patients had normal findings after pathological examination on the endometrial tissue samples. Conclusion: Evaluating the uterine cavity before the IVF cycle is necessary to reach successful outcomes. Undetected intrauterine lesions are frequently observed during hysteroscopy in asymptomatic patients previously examined by conventional methods. Hysteroscopy may be a reasonable approach to assess and restore the uterine cavity in patients undergoing the first IVF cycle.